A Charlie Brown Christmas [videorecording (Blu-Ray)] - Schulz, Charles M. (Charles Monroe), 1922-2000; Guaraldi, Vince ([publisher not identified], 2009)
Lights are twinkling red and green, but Charlie Brown has the Yuletide blues. To get in the holiday spirit, he takes Lucy's advice and directs the Christmas play. And a Christmas play needs a proper Christmas tree. But everyone makes fun of the short, spindly evergreen that Charlie brings back - that is until the real meaning of Christmas works is magic.